Mechanism development and experimental validation of self-centering nonlinear friction damper. (15th July 2023) - Yang, T.Y.; Zuo, X.; Rodgers, G.W.; Bagatini-Cachuço, F.
Highlights: A novel self-centering nonlinear friction damper is proposed. Detailed theoretical equations for the force displacement relation are presented. Experimental tests were conducted. The damper can be efficiently tuned to achieve different performances. A design procedure has been developed. Abstract: Current seismic engineering philosophy focuses on preserving life by guaranteeing that structural components can dissipate earthquake energy through inelastic cycles. Recent seismic events have shown that such a practice might lead to significant financial losses, downtime, and further social impacts. Alternatively, recent efforts have changed this paradigm towards next-generation seismic design solutions. This new philosophy adopts innovative energy dissipation devices to protect structural components, hence ensuring life safety with few impacts on the building's functionality. This way the structure can be inspected and/or repaired immediately after the earthquake with only minor disruptions. This paper presents a novel self-centering energy dissipation device, named the Self-Centering Nonlinear Friction Damper (SCNFD). The SCNFD utilizes pre-compressed double-acting spring cases attached to a pivot hinge with slotted holes to provide self-centering capacity, while friction pads dissipate energy. The proposed SCNFD is fully customizable as the springs and friction pads can be adjusted and/or replaced after inspection. The first part of the paper presents the SCNFD mechanism in detail and the set of equations that govern its response characteristics. The second part discusses the prototype validation with cyclic experimental tests, where its results indicate the proposed equations are well suited to model the SCNFD response. The third part presents a detailed parametric study to quantify the effects of different parameters on the SCNFD response. Finally, the last part includes a design methodology so that engineers can easily define the sizes of SCNFD components to achieve the desired target performance for using in different applications.